Robotic Ureteral Reconstruction in the Pediatric Population - Bilgutay, Aylin N.; Kirsch, Andrew J. (Frontiers in Pediatrics, 2019)
ABSTRACT Robot-assisted laparoscopic (RAL) surgery is a safe, minimally invasive technique that has become more widely used in pediatric urology over recent decades. With several advantages over standard laparoscopy, robotic surgery is particularly well suited to reconstructive surgery involving delicate structures like the ureter. A robotic approach provides excellent access to and visualization of the ureter at all levels. Common applications include upper ureteral reconstruction (e.g. pyeloplasty, ureteropelvic junction polypectomy, ureterocalicostomy, and high uretero-ureterostomy in duplex systems), mid-ureteral reconstruction (e.g. mid uretero-ureterostomy for stricture or polyp), and lower ureteral reconstruction (e.g. ureteral reimplantation and lower ureter-ureterostomy in duplex systems). Herein, we describe each of these robotic procedures in detail. INTRODUCTION Many considerations are involved in choosing surgical approach. Compared to open surgery, robotics offer several advantages including smaller incisions and more rapid convalescence. RAL surgery may, however, be difficult or even impossible in very small patients, in whom pure laparoscopic intervention may be preferred. Pure laparoscopy allows for even smaller incisions than robotic surgery, with ports as small as 2-3 mm available. Another disadvantage of robotic surgery is increased cost compared to pure laparoscopic or open approaches. Benefits of robotic surgery include wristed movements and magnified vision, making it the ideal approach for delicate reconstructive procedures. Robotics continue to enjoy expanding applications and growing popularity among urologists and patient families alike.